THE ROLE OF SOCIAL ECONOMIC LAW IN ENSURING HEALTH RIGHTS FOR PETTY THEFT OFFENDERS: A STUDY AT A CORRECTIONAL INSTITUTION - Gunawan Widjaja (CV. Adiba Aisha Amira, 2025)
This research aims to analyse the role of social economic law in guaranteeing the right to health for petty theft offenders in correctional institutions through a literature review. The right to health is a human right guaranteed by Law No. 12 of 1995 on Corrections and various related regulations, which requires the state to provide proper health services without discrimination against prisoners. However, implementation in the field still faces various obstacles, such as budget constraints, lack of medical personnel, inadequate health facilities, as well as bureaucratic constraints and overcapacity of prison residents. The results of the study show that the role of social economic law is very important in encouraging fair resource allocation and affirmative policies to fulfil the health rights of prisoners, especially vulnerable groups such as petty theft offenders who generally come from weak economic backgrounds. This study recommends the need for budget restructuring, strengthening cross-sectoral coordination, and developing prisoner empowerment programmes so that health rights can be fulfilled optimally and sustainably in the correctional environment.